Characterization and operational stability of EJ276 plastic scintillator-based detector for neutron spectroscopy. (1st October 2021) - McCormack, O.; Giacomelli, L.; Croci, G.; Muraro, A.; Gorini, G.; Grosso, G.; Pasqualotto, R.; Perelli Cippo, E.; Rebai, M.; Rigamonti, D.; Tardocchi, M.
Abstract: A state-of-the-art EJ276 plastic scintillator-based detector for neutron spectroscopy has undergone detailed characterization both in a controlled laboratory and on-site at the SPIDER negative ion source facility in Padua. The device will be used for the spectroscopy of 2.5 MeV neutrons produced from Deuterium-Deuterium fusion reactions occurring inside the SPIDER beam dump. A plastic based scintillator with neutron/gamma discrimination has some key advantages over the commonly used organic liquid scintillators with regards economic cost and handling safety. The purpose of this characterization is to determine the operational functionality and reliability of this new breed of detector material. Several tests were performed to verify expected operation with regards to signal reproducibility, long-term stability, and pulse shape discrimination (PSD) capabilities. It was found that the detector system (EJ276 scintillator + photomultiplier tube) performed well in terms of reproducibility and PSD, however the long-term stability of the scintillator light output was seen to diminish considerably over time (>50% decrease) and must be consistently monitored in order to have an accurate conversion scale needed for energy spectroscopy.